2009
DOI: 10.4103/0378-6323.48658
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of dermatophytosis in Tehran, Iran, from 2000 to 2005

Abstract: This study identifies the epidemiologic trends and the predominant organisms causing dermatophytosis in Tehran, Iran. These data can be used to ascertain the past and present trends in incidence, predict the adequacy of our current pharmacologic repertoire and provide insight into future developments. Consideration of the current epidemiologic trends in the incidence of cutaneous fungal pathogens is of key importance to investigational effort, diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 27 publications
4
38
2
2
Order By: Relevance
“…They also found a relationship between the spread of dermatophytosis and livestock infected with dermatophytes. The same results have been reported by several authors in different provinces in Iran (Dehghan et al, 2009;Khosravi et al, 1994;Sepahvand et al, 2009;Bassiri-Jahromi et al, 2009;Falahati et al, 2003;Pakshir et al, 2006). Finally, this study showed the importance of cattle ringworm in Sarab city and revealed the dominant role of T. verrucosum in cattle dermatophytosis.…”
Section: Discussionsupporting
confidence: 91%
“…They also found a relationship between the spread of dermatophytosis and livestock infected with dermatophytes. The same results have been reported by several authors in different provinces in Iran (Dehghan et al, 2009;Khosravi et al, 1994;Sepahvand et al, 2009;Bassiri-Jahromi et al, 2009;Falahati et al, 2003;Pakshir et al, 2006). Finally, this study showed the importance of cattle ringworm in Sarab city and revealed the dominant role of T. verrucosum in cattle dermatophytosis.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the variability of fungal species by geographic regions in 1990s, zoophilic fungi such as T. verrucosum overwhelmed the anthropophilic across some regions of the country, including certain endemic areas [14][15][16]. However, today anthropophilic T. mentagrophytes (T. interdigitale), Epidermophyton floccosum, and T. rubrum are the main pathogens in Iran [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Dermatophytes, yeasts, and non-dermatophyte moulds are known as causative agents of cutaneous fungal infections (1,2). It is estimated that they affect more than 20-25% of people all over the world (3).…”
Section: Introductionmentioning
confidence: 99%